The correlation analysis between preoperative cerebral small vessel disease and carotid plaque echo characteristics - Zhou, Yanqing; Yan, Pianpian; Guo, Shengwen; Huang, Yiting; Jiang, Lulu (Frontiers in Neurology, 2025)
PurposeThis study explores the correlation between carotid plaques and cerebral small vessel disease (CSVD).MethodA total of 167 patients were divided into CSVD (n = 119) and Non-CSVD (n = 48) groups. Various clinical variables, including body mass index (BMI), coronary artery disease, hypertension, and carotid plaque echo characteristics, were evaluated using multivariate logistic regression analysis.ResultsThe analysis revealed that carotid isoechoic plaques (OR = 2.139, 95% CI 1.421–3.219, P < 0.001) and hypoechoic plaques (OR = 1.687, 95% CI 1.206–2.359, P = 0.002) are independent risk factors for CSVD. Other variables such as BMI, coronary artery disease, hypertension, and hyperlipidemia did not reach statistical significance.ConclusionThe presence of carotid isoechoic and hypoechoic plaques significantly increases the risk of CSVD, highlighting the importance of carotid imaging in assessing stroke risk and guiding clinical management.